Język kaszubski jako element narodowotwórczy - Jabłoński, Artur (Postscriptum Polonistyczne, 2020)
Kashubian, as a Proto-Slavic dialect, was similar to the Greater Poland and Lesser Poland dialects which with time provided the foundations for the Polish language. However, as early as in the 13th century, differences became noticeable resulting from the autonomous development of Kashubian on the periphery of the Slavic world. Language is one of the most important ethnic building elements manifested by the Kashubian people since the dawn of ethnic emancipation which started in the mid-19th century, when Florian Ceynowa, physician and father of Kashubian national empowerment, created the first Kashubian alphabet, normalised the spelling, compiled the grammar rules and started to write journalistic, scientific and literary texts. In the past, the Kashubians had long lacked the conviction that their vernacular had value. The joint work of many communities, undertaken for the sake of the linguistic status of Kashubian in the 1990s, led first of all to a change of the attitude of the users towards their own language, and subsequently to its recognition as a separate Slavic language. Kashubian was granted the political and legal status of a regional language in 2005. It satisfies mainly those who have adopted a hybrid identity characterised by being Kashubian in the regional aspect and Polish in the national aspect. However, that status is insufficient for Kashubians representing the national option, who identify themselves as Polish citizens of Kashubian nationality.